A proposal for a new model of shariah compliant hotels / Zakiah Samori … [et al.] - Samori, Zakiah; Abd Rahman, Fadilah; Sabtu, Noorsalwati; Yaakob, Mohd Ashrof Zaki; Khalid, Mohammad Mahyuddin (Research Innovation Business Unit, 2014)
Halal hub is a concerted effort among Islamic countries such as halal food, halal manufactures, halal pharmaceutical, halal cosmetics, halal packaging, halal logistic products as well as halal services from all over the world. In response to the emergence of halal hub in various sectors including those in the hotel and tourism industry, it is widely acknowledged fact that the halal hotels had been recognized in many countries particularly those in the Middle East. This tremendous development in the hotel industry caused by the drastic dropped of tourists from Middle East to UK after Sept 11, 2000 tragedy thus Muslim tourists shifted to another Muslim countries including Malaysia. Given the fact the demand of Shariah Compliant Hotels is increasing, a new viable and sustainable model of Shariah Compliant Hotel must be formally designed and established. This model of Shariah Compliant Hotels is developed to fulfil the gap between an International perspective on examining the features of Shariah Compliant Hotel particularly those of the Middle East countries and the components associated with the Shariah Compliant Hotel in Malaysia. The model is designed via analysis of the literatures concerning the key components of Shariah Compliant Hotel and through a comparative analysis between the features of the existing Shariah Compliant Hotel in selected Middle East countries and Malaysia. This model is very unique in itself as it is designed as a result of harmonisation between the review of the literatures on the Shariah Compliant Hotel’s characteristics with the characteristics of Shariah Compliant Hotel as practised in the Middle East countries and Malaysia through a comparative analysis. On top of that, it is further adapted to accommodate with local culture, norms and values. Given the facts that interest and demand for Shariah Compliant Hotel has already taken place in Malaysia and abroad, this new model of Shariah Compliant Hotel would serve as a basis for the hotel industry players in their quest to setting up Shariah Compliant Hotel.